With your own two hands: Self-discovery through music - Bernstein, Seymour (New York G. Schirmer, 1981)
This best-seller by the nationally acclaimed pianist is a realistic program for conquering nervousness, sharpening concentration, and enhancing coordination. Bernstein observes that musicianship requires the same talents used in any activity, and shows how to develop a dedication to practice that can harmonize the musical and personal self.